A implementação do programa nacional de valorização dos trabalhadores em educação – profuncionário no Paraná - Pedroso, Jociane Martins (2015)
The National Program of Education Workers Formation (Profuncionário) is a Federal Government program that has been spread through many Brazilian states, including Paraná, since 2005. MEC, by the National Educational Board, has included the National Syllabus to the Professional area 21 (Services and Support in schools), the School Office allocations, School Food, Technology Educational Tools and School Structure. The main goal of this assignment was to reflect on the linkage between this program and the concepts needed to the development of workers since the 90´s. The specific objectives were:a) to study the context of emergency of the policies used to form School Workers in Paraná b) to understand the formation of those workers and the demand of the State Schools of Paraná c) to analyse the process of improvement of Education workers in the context of the formation of Paraná workers. This article is organized in three chapters: in the first one, there is an explanation about social and educational policies and the changes in the work world, as well as the process of union organizations. The terms "school workers", "education workers" and "school employees" are presented based on Brazilian and the State of Paraná Education laws. The second chapter had the intention of understanding the implementation of the Profuncionário program. There is an analyses about the demand for those professionals known as Educational Agents I and II. In the third chapter was made an analyses about the pedagogical organization and about the work that´s been happening in the process, focusing on the Notebooks, and detaching the concept of skills required in the 1990's and in the early 21st century. Through this study, it was possible to understand that this program emerges as a flag of union workers and education professionals, as well as it expresses the historical an political context that has produced it. In Paraná State Schools in 2013, 90% of the workers of Quadro Próprio do Poder Executivo (QPPE) and of Quadro dos Funcionários da Educação Básica (QFEB) graduated or were attending the program.